The impact of parental hoarding on the lives of children: Interviews with adult offspring of parents with hoarding disorder - Rees, Clare; Valentine, S.; Anderson, R. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 The Australian Psychological Society. Background: Hoarding disorder is associated with significant impairment for the individual such as lower rates of employment and social isolation. However, less is known about the impact of this condition on the children of people with hoarding disorder (HD). No qualitative research to date has focussed exclusively on the experiences of adult offspring of parents with hoarding difficulties. The present qualitative study set out to investigate the experiences of adult offspring of parents with hoarding difficulties, exploring the present, and longer-term impacts of parental hoarding. Method: Seven females between the ages of 35 and 62years were interviewed using a semi-structured format; all reported parental hoarding within the clinically significant range. Interpretative phenomenological analysis was utilised to analyse interview transcripts. Results: Four superordinate themes were extracted from the data: psychological and emotional outcomes, coping strategies, perceptions of parental hoarding, and impact on relationships. Conclusions: The research demonstrated the significant impacts of parental hoarding on their offspring, both individually and on a relational level. The outcomes of this research provide clinical implications for working with this population, as well as suggestions for future research.